Navigating the pandemic: an exploration of health behavioral dynamics among Asian Americans during COVID-19 - Li, Xiao; Mitchell, Jordan; Decker, Phillip; Park, Jae Man (International Journal of Public Health Science (IJPHS), 2024)
The COVID-19 pandemic brought Asian Americans sharply into focus, revealing both the strengths and vulnerabilities within this community. Despite a myriad of studies on their experiences and health disparities during the outbreak, gaps persist in our understanding of their health literacy, beliefs, and healthcare behaviors. Leveraging the snowball sampling method, our study engaged 20 diverse Asian Americans, delving into facets ranging from English proficiency and health literacy to cultural health beliefs and preventive behaviors. Notably, participants exhibited high English proficiency and health literacy. Their health choices, shaped by their Asian heritage, showcased a proactive approach to combating COVID-19. Most did not defer or sidestep healthcare, underlining their commitment to well-being. These insights underscore the resilience and adaptability of the Asian American community. By decoding their health behaviors and beliefs, our study aims to refine public health strategies, ensuring they resonate not just with Asian Americans but potentially with other ethnic cohorts amidst global health crises.